Condition monitoring of brushless synchronous generators using wireless sensors - Sampath Kumar Padmanabhan (Nanyang Technological University, 2019)
The conventional condition monitoring systems for Brushless synchronous generators (BLSGs) are predominantly based on externally available signals, while the internal signals, especially on the rotor, remain relatively unexplored. Given that rotor-based faults have been identified as more critical for the BLSG, the measurements made internal to the machine could prove to be more sensitive compared to these external measurements. To access these internal signals, wireless sensors offer an effective solution in terms of cost and ease of deployment. In realizing such a Wireless-Condition Monitoring System (Wi-CMS), the two key challenges which need to be addressed are: (1) establishing reliable access to internal signals and (2) demonstrating the improvement in diagnostic performance with the internal signals. In this thesis, an experimental feasibility study to evaluate the wireless RF link performance is presented. An evaluation of fault indicators is conducted and using a data-based approach, the improvement in diagnostic performance achieved by Wi-CMS is presented.